The Development of Essay Writing Skills Through the CIRC Cooperative Learning Model Integrated with Buddhist Teaching Principles for Grade 6 Students at Ban Daeng Noi School, Khon Kaen Province - Kittisobhaṇo (Singthong), Phrakhrupalad Theerapong; Sribunrueang, Pacharakit; Phrakrukhamphithammanuwat (Journal of Buddhist Education and Research (JBER), 2026)
This research aimed to: 1) develop a learning management plan on essay writing using the Cooperative Integrated Reading and Composition (CIRC) learning model integrated with Buddhist teaching principles to meet the 80/80 efficiency criterion; 2) compare students’ learning achievement in essay writing before and after instruction; and 3) examine students’ satisfaction with the learning management plan. The target group consisted of 15 Grade 6 students at Ban Daeng Noi School, Khon Kaen Province. The research instruments included a learning management plan on essay writing using the CIRC cooperative learning model integrated with Buddhist teaching principles, a pre-test and post-test achievement test, and a student satisfaction questionnaire. Data were analyzed using mean, standard deviation, and dependent t-test. The findings revealed that: 1) the learning management plan achieved an efficiency level of 82.67/83.33, which exceeded the established criterion of 80/80; 2) students’ learning achievement in essay writing significantly improved after the implementation of the learning model. The mean pre-test score was 15.47 (S.D. = 2.59), while the mean post-test score was 25.00 (S.D. = 3.18), with the post-test score being significantly higher than the pre-test score at the .05 level; and 3) students’ overall satisfaction with the learning management plan was at the highest level (x̄ = 4.26). Instructional activities received the highest mean score (x̄ = 4.83), followed by assessment and evaluation (x̄ = 4.78), instructional media and learning materials (x̄ = 4.53), and content (x̄ = 4.35). The findings indicate that the CIRC cooperative learning model integrated with Buddhist teaching principles effectively enhanced students’ essay writing skills and promoted positive learning experiences.